Strategic Determinants of Transfer Pricing in Indonesian Non-Financial Firms - Imar Ardeliani; Badingatus Solikhah (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2025)
This study aims to analyze the effect of intangible assets, tax minimization, capital intensity, and corporate governance on transfer pricing in non-financial companies in Indonesia. Panel analysis with a fixed effects model was used with a sample of 4,220 observations. The results show that intangible assets and capital intensity increase the tendency for transfer pricing, while stronger corporate governance is able to suppress it. Meanwhile, tax minimization is not proven to have a significant effect. These findings confirm that asset structure and the effectiveness of internal oversight are more dominant than tax motivation.